Payback time? Student debt and loan repayments: what will the 2012 reforms mean for graduates? - Claire Crawford; Wenchao Jin (Institute for Fiscal Studies (IFS), 2014)
This report updates and extends the previous IFS work to examine the consequences of these changes for graduates. In particular, we use a new model of graduate earnings and repayments and explore in more detail the pattern and size of loan repayments made, including by different types of graduates.
Keywords: 330